Tarih Pedagoji Programı Öğrencilerinin Tarih Kavramına İlişkin İnançlarının Metafor Analizi Yoluyla İncelenmesi / Examination of History Pedagogy Programme Students’ Beliefs about The Concept of History Through Metaphor Analysis - Demircioğlu, Ebru; Kantekin, Samet (Journal of History Culture and Art Research, 2019)
Abstract The aim of this study is to examine and present the beliefs which about concept of history of through metaphor analysis to history teacher candidates who in the history pedagogy programme of students in Trabzon University at Fatih Education Faculty. The survey method was used in the study and the data were obtained through the metaphor survey. Via metaphors, the two things that are not alike by acting on the common characteristics, similar features tried to create with analogy. This research is based on a qualitative approach and the study was carried out with the students attending the history pedagogy program of Fatih Faculty of Education. A total of 74 teachers, 37 girls and 37 boys, participated in the survey. Since the entire universe intended to be reached, the study doesn’t require a sample. The data were obtained through open-ended questionnaires. Prior to the study, participants who history teacher candidates were informed about what the metaphor and how the metaphor is produced is by giving examples from different fields. The questionnaire form is distributed to each of the teacher candidates and filling gaps produce metaphors coherent the expression which history is like ……...". Because ………. In the research the concept of “because” was by given participants want to present a reason for their generate metaphors about the concept of history. These data were evaluated according to the content analysis which is a qualitative data analysis approach. In this framework, metaphors were first read and then coded process was done. Then, conceptual categories were constitute from the obtained codes. In the light of the data obtained. In the light of the data obtained, produced 201 valid metaphors related to the concept of history by history teacher candidates. 8 main categories are produced from these metaphors. These are: ‘‘history which illuminates the future and guide’’, ‘‘history as unknown’’, ‘‘history as illuminating past’’, “accumulated, increasing history’’, ‘‘history as transmitter proud’’, ‘‘history as records everything’’, ‘‘history as researchers’’ and ‘‘subjective history’’. In the light of the data obtained İt can be seen that participated in the study who history teacher candidates doesn’t produce enough metaphor in spite of extract a four year history education. Whereas, it is seen that the history teacher candidates were mostly able to produce metaphors especially related to the future enlightenment of history and the extent of taking lessons from history. In contrast, it is understood that teacher candidates don’t produce metaphors in relation to historical thinking skills, time, chronology, cause- result, empathy and critical thinking. In addition to this, it is also the result of this research that the candidates are unable to produce metaphors in relation to the scientific research aspects of history and the scientific research skills. In other words, it is seen that the history teacher candidates who participated in the research have looked at history from a traditional perspective. Öz Bu çalışmanın amacı, Trabzon Üniversitesi Fatih Eğitim Fakültesi Tarih Pedagoji Programı’nda öğrenim görmekte olan tarih öğretmen adaylarının tarih kavramına ilişkin inançlarını metafor analizi yoluyla inceleyip ortaya koymaktır. Araştırmada survey yöntemi kullanılmış olup veriler metafor anketi yoluyla elde edilmiştir. Metaforlar yoluyla, birbirine benzemeyen iki şeyin ortak özelliklerinden hareket ederek, benzer özellikleri benzetmeyle ortaya çıkarılmaya çalışılmıştır. Bu araştırma nitel bir anlayışla yürütülmüştür. Çalışma Trabzon Üniversitesi Fatih Eğitim Fakültesi Tarih Pedagoji Programı’na devam eden öğrencilerle gerçekleştirilmiştir. Araştırmada kullanılan ankete 37 kız ve 37 erkek olmak üzere toplam 74 öğretmen adayı katılmıştır. Çalışmada veriler açık- uçlu bir metafor anketi yoluyla elde edilmiştir. Öğretmen adaylarına çalışma öncesinde metaforun ne olduğu ve nasıl benzetme yapıldığıyla ilgili farklı alanlardan örnekler verilmiş ve böylece kavramın ne olduğu ve nasıl üretildiğiyle ilgili bilgilendirilmeleri sağlanmıştır. Öğretmen adaylarından her birine anket formu dağıtılmış ve “Tarih .… gibidir. Çünkü ....” ifadesindeki boşlukları doldurarak metafor üretmeleri istenmiştir. Araştırmada “çünkü” kavramına da yer verilerek, katılımcıların tarih kavramına ilişkin ürettikleri metaforlar için bir gerekçe sunmaları istenmiştir. Elde edilen bu veriler, nitel veri çözümleme yaklaşımı olan içerik analizine göre değerlendirilmiştir. Bu çerçevede öncelikle metaforlar okunmuş ve ardından kodlama işlemi yapılmıştır. Daha sonra elde edilen kodlardan kavramsal kategoriler oluşturulmuştur. Elde edilen verilerin ışığında tarih öğretmen adayları tarafından tarih kavramına ilişkin 201 geçerli metafor üretildiği görülmektedir. Üretilen bu metaforlardan 8 ana kategori üretilmiştir. Bunlar: “geleceği aydınlatan ve rehber olan tarih”, “bilinmez olarak tarih”, “geçmişi aydınlatan olarak tarih”, “biriken çoğalan tarih”, “gurur verici olarak tarih”, “her şeyi kaydeden tarih”, “araştırmacı olarak tarih”, ve “öznel tarih”tir. Elde edilen verilerin ışığı altında, çalışmaya katılan tarih öğretmen adaylarının dört yıllık bir tarih eğitimi almalarına karşın yeterli düzeyde metafor üretemedikleri görülürken, öğretmen adaylarının ağırlıklı olarak özellikle tarihin geleceği aydınlatması ve tarihten ders alınması boyutuyla ilgili metafor ürettikleri görülmektedir. Buna karşın, öğretmen adaylarının tarihsel düşünme becerileri, zaman, kronoloji, neden-sonuç, empati ve eleştirel düşünmeyle ilgili olarak metafor üretmedikleri anlaşılmaktadır. Bunun dışında tarihin bilimsel araştırma yönü ve öğrencilere kazandırabileceği bilimsel araştırma becerileriyle ilgili olarak da adayların metafor ortaya koyamadıkları bu araştırmada ortaya konan diğer bir sonuçtur. Başka bir deyişle araştırmaya katılan tarih öğretmen adaylarının tarihe geleneksel bakış açısıyla baktıkları görülmektedir.